Women’s human dignity and al-Asmā’: A maqāṣid syarī‘ah perspective by Yudian Wahyudi (Pusat Studi Gender dan Anak, 2026)
Gender disparities in higher education remain a significant issue, particularly evident in the low participation of women at the highest level of the academic career ladder, namely as lecturer. The discussion on women caught many attentions in the past and present, thus this study chose Yudian Wahyudi, an Indonesian scholar who has written extensively on maqāṣid syarī‘ah, including women issues. The study aims to discuss his intellectual contributions regarding the human dignity of women and the role of al-asmā’ (specific expertise) in honouring women. As qualitative research, this study is a literature review employing a hermeneutic-conceptual approach. Primary data sources were obtained from Yudian Wahyudi’s works, interviews, and supporting literature on maqāṣid syarī‘ah, gender exegesis, and women’s equality in higher education. Data analysis was conducted by tracing key concepts in his thought, integrative tauḥīd, Indonesian identity, lailatul qadr, qiwāmah, and al-asmā’, and then linking them to the issue of women’s human dignity. This paper argues that there are two main foundations that Yudian consistently applies to social discourses, specifically regarding the position of women: 1) The application of Integrative tauḥīd, and 2) the application of the Indonesian context. Yudian interprets lailatul qadr as a symbol of liberation from all forms of inequality and argues that empowering women is essential for advancing civilization. As for al-asmā’, it is understood as achievements produced by women across all sectors of civilization. Through a maqāṣid syarī‘ah approach, he promotes a contextual and socially beneficial interpretation of Islam that strengthens women's human dignity.